Lessons from a case study: Burkina Faso - Turowska, Zuzanna; Becquey, Elodie (International Food Policy Research Institute, 2020)
Burkina Faso has made impressive improvements in nutrition over the last 30 years. Stunting rates among children under five have declined (from 45% in 1998/99 to 25% in 2018) and known nutrition drivers have improved. As a sector, nutrition has risen among national priorities, enacted several nutritionspecific policies, and increased funding. Despite these achievements, many challenges remain. This brief— based on research from the Stories of Change in Burkina Faso report—aims to tell the story of Burkina Faso’s success in nutrition, identify its challenges, and provide evidence-based recommendations to address challenges now and in the future.